2019
DOI: 10.3390/cells8040367
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Mitochondrial Biology in the Oral Mucosa of Chilean Children with Autism Spectrum Disorder (ASD)

Abstract: Autistic Spectrum Disorder (ASD) is characterized by the impairment of socio-communicative skills and the presence of restricted and stereotyped behavior patterns. Recent researches have revealed the influence of mitochondrial physiology on the development of ASD. Several research groups have identified defects in respiratory complexes, coenzyme-Q10 deficiency, increased oxidative damage, decreased of superoxide dismutase (SOD2). A study on the influence of mitochondrial physiology on the development of ASD ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 58 publications
(101 reference statements)
4
27
1
Order By: Relevance
“…This is in line with the fact that a shift toward fusion enables the cell to fulfill energy demand through extended mitochondrial filaments and enhanced cristae density 7 . Of note, our results on the gene expression of the mitochondrial dynamics factors are comparable with those showed in a recent study from another group that reported an upward trend in the expression of the MFN1, dynamin‐like 120 kDa protein, mitochondrial (OPA1), DRP1, and FIS1 genes coupled with significant increased expression of MFN2 gene in the oral mucosa of ASD children 35 . However, in contrast to our data, Tang et al 36 found an altered expression of mitochondrial dynamics proteins in ASD brain, with decreased levels of MFN1, MFN2, OPA1, and increased levels of DRP1 and FIS1.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with the fact that a shift toward fusion enables the cell to fulfill energy demand through extended mitochondrial filaments and enhanced cristae density 7 . Of note, our results on the gene expression of the mitochondrial dynamics factors are comparable with those showed in a recent study from another group that reported an upward trend in the expression of the MFN1, dynamin‐like 120 kDa protein, mitochondrial (OPA1), DRP1, and FIS1 genes coupled with significant increased expression of MFN2 gene in the oral mucosa of ASD children 35 . However, in contrast to our data, Tang et al 36 found an altered expression of mitochondrial dynamics proteins in ASD brain, with decreased levels of MFN1, MFN2, OPA1, and increased levels of DRP1 and FIS1.…”
Section: Discussionsupporting
confidence: 90%
“…ASD/No‐DR participants demonstrated less mtDNA damage compared to ASD/DR. Although mtDNA damage has not been examined in ASD in the past, other studies have noted an increased mtDNA copy number in leukocytes 6,7,43–45 and buccal mucosa 46 . An increase in overall mtDNA content is believed to be a compensatory reaction that maintains adequate wild‐type mtDNA in the face of high levels of oxidative stress which itself can damage and cause deletions in mtDNA 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, abnormalities in the respiratory electron transport chain during the first stage of development may be involved in the etiology of neurodevelopmental disorders. Interestingly, dysfunctions have been found in nuclear genes that encode for proteins specifically involved in mitochondrial fission and fusion, such as MFN1, MFN2, OPA1, and that are involved in mitochondrial dynamics [30]. Mitochondria are dynamic organelles, constantly changing their morphology or shape by undergoing fission (fragmentation) and fusion (elongation).…”
Section: Discussionmentioning
confidence: 99%
“…Carrasco M. et al, 2019 [30] 12 children with ASD (11 male, 1 female) 12 children without ASD Descriptive transactional and non-probabilistic design to study mtDNA in the oral mucosa of children with ASD mtDNA analysis performed with quantitative PCR (qPCR). Genotyping of the Ala16Val-SOD2 Single Nucleotide Polymorphism (SNP) polymorphism was performed by PCR using the DNA from the oral mucosa sample and a "Tetra-Primer ARMS-PCR" assay.…”
Section: Patowary Et Almentioning
confidence: 99%
See 1 more Smart Citation